Study of Mathematical Activities in “Rumah Tuo” - Reri Seprina Anggraini; Ferinaldi Ferinaldi; Nurfauziah Nurfauziah; Wahyu Widada; Dewi Herawaty (International Journal of Trends in Mathematics Education Research, 2022)
Mathematics learning still tends to be structuralistic and mechanistic. It resulted in students' difficulties and errors in understanding mathematical concepts and principles. Whereas mathematics is a human activity that is always in contact with their culture. One of the cultures that becomes the starting point for learning mathematics is a traditional house, such as the “Rumah Tuo”. The purpose of this study was to describe the mathematical activity at the Rumah Tuo. This type of research is a qualitative-research with an ethnographic approach. The research instrument used in the form of observation, interviews, and documentation. The results of this study are that there are mathematical activities carried out at Rumah Tuo, namely counting activities using Gantang Biheh, measuring activities in making poles in the form of a 16-sided prism, and designing traditional houses in such a way that they can be shaped like ancient means of transportation, namely ships. The conclusion of this research is that there are three mathematical activities through the “Rumah Tuo” culture, namely measuring, designing and calculating.